A Review of IoT-Based Wearable Sensor Systems for Healthcare Monitoring (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
Many sectors have benefited greatly from the Internet of Things (IoT) during the last few decades. More individuals now have access to healthcare thanks to recent developments in the field, which has in turn improved the health of those receiving it. In the future, wearable sensors and IoT will be effortlessly integrated into healthcare. The numerous IoT topologies, diverse techniques of data processing, transport, and computing paradigms are thoroughly discussed in this paper. An overview of several IoT-assisted wearable sensor systems is provided, together with information on their numerous uses in healthcare and the benefits they provide for society as a whole. Additionally, a comparison of all healthcare wearable technologies is presented using data from numerous research and development projects. It also discusses the specific issues that need to be addressed in order to optimize these systems for healthcare and the various future implementations of architecture and technology that can be made in order to improve the healthcare industry, as well as the common problems that IoT-assisted wearable sensor systems face.